Efficient XML queries and updates encoding scheme in the presence of access control using fractional numbers - Nooshabadi, Meghdad Mirabi (2013)
As XML is emerging as a de facto standard for sharing and exchanging data over the internet, access control for XML data has become an important research topic. Several XML access control mechanisms have been proposed to enforce a finegrained access control for querying XML data. However, only a few researches are proposed to update the structure of XML data in the presence of a fine-grained access control. A way to accelerate the process of XML querying is to label the XML nodes in such a way that the structural relationships between two arbitrary XML nodes in the XML tree can be efficiently computed. However, if there is frequent demand for the XML data to be updated, most of the existing XML labeling schemes need to re-label preexisting XML nodes in order to keep the order of XML nodes in the XML tree, which is rather time consuming. In order to query and update XML data in the presence of a fine-grained access control, an accessibility map is required to determine the accessibility of XML nodes at runtime. Several researches have been done to compress the accessibility map in such a way that the accessibility of XML nodes can be rapidly determined but there is no effort to compress the accessibility map in dynamic XML environment where the accessibility of XML nodes can be updated frequently. In this thesis, first we propose a novel XML encoding and labeling scheme based on fractional numbers to encode and label the XML nodes in the XML tree. Our proposed XML encoding and labeling scheme is able to determine the structural relationships between two arbitrary XML nodes in the XML tree and to eliminate the process of re-labeling pre-existing nodes during the process of XML updating. The experimental results demonstrate that our proposed XML encoding and labeling scheme is more efficient than existing XML encoding and labeling schemes for XML querying and updating. Secondly, we propose a Dynamic Compressed Accessibility Map called DCAM to compress the accessibility map with rapid determination of accessibility of XML nodes at runtime in such a way that it needs minimum maintenance cost to be used in dynamic XML environment. In order to determine the structural relationships between XML nodes in the DCAM, we label the XML nodes in the XML tree as well as the XML nodes in the DCAM with our proposed XML encoding and labeling scheme. The experimental results demonstrate that the DCAM is more efficient than the CAM in compressing the accessibility map.